Analisis Pengaruh Tiktok pada Anak SD : Hiburan yang Menyenangkan atau Gangguan Yang Berbahaya - Nazumi Anggofi; Latifah Hairani; Lusi Afrima; Ari Suriani; Afriza Media (STIKes Ibnu Sina Ajibarang, 2025)
The development of digital technology has changed the way children interact with the world, one of which is through social media platforms such as TikTok. This application has become very popular among elementary school-aged children because it presents short video content that is interesting, fast, and easy to consume. This article aims to analyze the influence of TikTok on elementary school children through a literature review approach of various recent research results. The focus of the analysis includes the impact of TikTok use on children's psychological, social, reading habits, and politeness values. Based on the results of the review, it was found that the use of TikTok has two sides: on the one hand it can increase children's creativity, self-confidence, and communication skills; but on the other hand it also has the potential to cause a decrease in politeness, social empathy, learning focus, and the emergence of impulsive behavior and digital addiction.